2015
DOI: 10.1007/s12094-015-1296-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of enhanced recovery program for patients undergoing partial laparoscopic hepatectomy of liver cancer

Abstract: This study suggests that ERAS is feasible and safe for laparoscopic hepatectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(104 citation statements)
references
References 40 publications
8
96
0
Order By: Relevance
“…ERAS can be always improved, all patients undergoing surgery can benefit from this programs . For patients who have liver diseases and require hepatectomy, whether laparoscopic surgery or laparotomy, liver tumor or hepatolithiasis, segmental hepatectomy or hemihepatectomy, ERAS programs can effectively accelerate the perioperative rehabilitation . However, the ERAS programs cannot be successfully implemented without multidisciplinary collaboration, and it is essential to have teamwork from the departments of surgery, anesthesia, nursing, nutrition, rehabilitation, and other departments …”
Section: Discussionmentioning
confidence: 99%
“…ERAS can be always improved, all patients undergoing surgery can benefit from this programs . For patients who have liver diseases and require hepatectomy, whether laparoscopic surgery or laparotomy, liver tumor or hepatolithiasis, segmental hepatectomy or hemihepatectomy, ERAS programs can effectively accelerate the perioperative rehabilitation . However, the ERAS programs cannot be successfully implemented without multidisciplinary collaboration, and it is essential to have teamwork from the departments of surgery, anesthesia, nursing, nutrition, rehabilitation, and other departments …”
Section: Discussionmentioning
confidence: 99%
“…Six studies were RCTs, 22,25,28,29,32,35 16 were case-control studies 2, 18, 21, 23, 24, 27, 31, 33, 36-42 and five prospective studies. 19,20,26,30,34 Eleven studies included both open and laparoscopic surgery in the study, 19-21, 23, 24, 27, 33, 35, 37, 39, 40 ten studies included only open liver surgery patients, 2, 18, 25, 26, 30-32, 34, 41, 42 five studies included only laparoscopic surgery patients, 22,28,29,36,38 whilst one study performed a separate analysis for laparoscopic surgery and open surgery. 21 A detailed characteristic of included studies is shown in Table 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Many authors have tried to study applications of ERAS protocols on liver surgeries. (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and showed ERAS protocol has significant benefit over standard protocols however large number studies and quality metaanalysis are still missing. Purpose of this metaanalysis to compare outcomes between ERAS and conventional group.…”
Section: Discussionmentioning
confidence: 99%